A Novel in vitro Model Delineating Hair Cell Regeneration and Neural Reinnervation in Adult Mouse Cochlea - Li, Wenyan; Quan, Yizhou; Huang, Mingqian; Wei, Wei; Shu, Yilai; Li, Huawei; Chen, Zheng-Yi (Frontiers in Molecular Neuroscience, 2022)
The study of an adult mammalian auditory system, such as regeneration, has been hampered by the lack of an in vitro system in which hypotheses can be tested efficiently. This is primarily due to the fact that the adult inner ear is encased in the toughest bone of the body, whereas its removal leads to the death of the sensory epithelium in culture. We hypothesized that we could take advantage of the integral cochlear structure to maintain the overall inner ear architecture and improve sensory epithelium survival in culture. We showed that by culturing adult mouse cochlea with the (surrounding) bone intact, the supporting cells (SCs) survived and almost all hair cells (HCs) degenerated. To evaluate the utility of the explant culture system, we demonstrated that the overexpression of Atoh1, an HC fate-determining factor, is sufficient to induce transdifferentiation of adult SCs to HC-like cells (HCLCs). Transdifferentiation-derived HCLCs resemble developmentally young HCs and are able to attract adult ganglion neurites. Furthermore, using a damage model, we showed that degenerated adult ganglions respond to regenerated HCLCs by directional neurite outgrowth that leads to HCLC-neuron contacts, strongly supporting the intrinsic properties of the HCLCs in establishing HCLC-neuron connections. The adult whole cochlear explant culture is suitable for diverse studies of the adult inner ear including regeneration, HC-neuron pathways, and inner ear drug screening.